DESIGN AUGMENTED REALITY FOR PROPERTY IN JIARMAH GROUP - Sintia Sintia; Yonky Pernando (LPPM STMIK Royal Kisaran, 2023)
Abstract: Augmented reality is a technology that combines the virtual world and the real world in the form of two-dimensional or 3D objects in real time. This study uses the markerless augmented reality method to display the object. This study uses the prototype method where researchers listen to customers, build or revise mockups and customer test drive mockups. This augmented reality application was created using the Blender, Unity, Sketchup Pro and Vuforia SDK applications. Making three-dimensional objects is made using Blender and Sketchup Pro while making applications using Unity and Vuforia SDK. The results of the research on the application that was made were tested using blackbox testing where the test results obtained